2010
DOI: 10.1111/j.1532-950x.2010.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator Vaginal Tape Inside Out for Treatment of Urethral Sphincter Mechanism Incompetence: Preliminary Results in 7 Female Dogs

Abstract: TVT-O was efficient in maintaining short term continence in 6 of 7 dogs affected with USMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 42 publications
0
47
0
1
Order By: Relevance
“…What remains unclear is the mechanism of action of the TVT‐O in dogs, with urethral pressure profiles demonstrating an increase in urethral resistance following tape placement, but in a proximal location to that of the tape (Claeys et al . ). One suggestion is that partial obstruction of the distal urethra results in a local increase in urethral resistance, another possibility is that loss of structural support of the urethra is a factor involved in the pathophysiology of USMI in some dogs and that this is addressed by the sling, although this appears improbable owing to the strong association of this factor with childbirth in women, which is not part of the problem in dogs.…”
Section: Urethral Sphincter Mechanism Incompetencementioning
confidence: 97%
See 1 more Smart Citation
“…What remains unclear is the mechanism of action of the TVT‐O in dogs, with urethral pressure profiles demonstrating an increase in urethral resistance following tape placement, but in a proximal location to that of the tape (Claeys et al . ). One suggestion is that partial obstruction of the distal urethra results in a local increase in urethral resistance, another possibility is that loss of structural support of the urethra is a factor involved in the pathophysiology of USMI in some dogs and that this is addressed by the sling, although this appears improbable owing to the strong association of this factor with childbirth in women, which is not part of the problem in dogs.…”
Section: Urethral Sphincter Mechanism Incompetencementioning
confidence: 97%
“…An initial cadaveric and experimental study demonstrated feasibility of the technique, with no significant complications and short‐medium term results in seven dogs appeared highly promising with six reported to be fully continent at a mean of 11∙3 months postoperatively (7 to 15 months) (Claeys et al . , ) . A more recent update on a cohort of 12 dogs followed for a mean of 74∙4 months revealed a drop in continence rate to only 40% in the long term (Claeys ).…”
Section: Urethral Sphincter Mechanism Incompetencementioning
confidence: 99%
“…Success rates of 80% are reported for the transobturator vaginal tape inside‐out and the percutaneously controlled urethral hydraulic occluder (Claeys et al. 2010a; Currao et al. ; Reeves et al.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical options are available where the response to medical management is unsatisfactory, or owners would prefer to avoid long‐term medical management. Surgical management of canine female USMI has been reported clinically using procedures including colposuspension (Holt 1990, Muir and others 1994, Rawlings and others 2001), urethropexy (Massat and others 1993, White 2001), urethral submucosal injections with either collagen (Arnold and others 1996, Barth and others 2005, Byron and others 2011), polytetrafluoroethylene (PTFE) (Arnold and others 1989) or extracellular matrix bioscaffold (Wood and others 2005), transobturator vaginal tape, inside out (TVT‐O) (Claeys and others 2010a, 2010b), Dacron ® coated Silastic ® sheet urethral sphincter (Dean and others 1989), and, most recently, a static hydraulic urethral sphincter (SHUS) (Rose and others 2009). The most common complications seen following all of these described surgical managements include persistent incontinence (immediate or delayed), dysuria, urinary obstruction, haematuria and recurrent urinary tract infection (UTI) (Arnold and others 1989, 1996, Holt 1990, White 2001, Barth and others 2005, Byron and others 2011).…”
Section: Introductionmentioning
confidence: 99%